Comparative Stability of Oral Vitamin K Liquids Stored in Refrigerated Amber Plastic Syringes. (June 2019) - Lawson, Sarah; Lewis, Paul; Peacock, Gina; Brown, Stacy
Background: Compounded vitamin K oral liquids may be useful in some patient populations, or when an appropriate solid dosage form is not available. While vitamin K oral liquid is typically prepared with sterile water for injection (SWFI), other compounding agents may be more palatable.Objective: To evaluate stability of compounded vitamin K liquids in SWFI, Ora-Sweet, simple syrup, cherry syrup, and SyrPalta stored in amber plastic oral syringes.Methods: Five types of compounded vitamin K liquids were prepared in triplicate—Ora-Sweet, simple syrup, cherry syrup, SyrPalta, and SWFI without flavoring; aliquoted into amber plastic oral syringes; and stored in a laboratory refrigerator (4.9°C to 5.4°C). On study days, 3 syringes from each batch were removed, diluted to assay concentration, and compared with a freshly prepared US Pharmacopeia reference solution. The samples and reference were analyzed using a previously validated high-performance liquid chromatography–ultraviolet method. Product stability was defined as 90% to 110% labeled amount. Results were further compared using a 2-way ANOVA (analysis of variance; P = .05) with post hoc Tukey's correction for multiple comparisons.Results: Vitamin K in SWFI, SyrPalta, and cherry syrup was stable for 21 days, 7 days, and 24 hours, respectively, under refrigeration in amber plastic oral syringes. Vitamin K in Ora-Sweet and simple syrup demonstrated high within-day variability and low potency. Statistically significant differences were detected between the SWFI formulation and all other vehicles.Conclusion: Vitamin K in SWFI is appropriate for longer-term storage of unit-dosed vitamin K; however, SyrPalta and cherry syrup may be used for short-term storage or immediate administration of vitamin K.